Thermostability of cardosin A from Cynara cardunculus L. - Pina, David G. (2003)
The structural stability of cardosin A, a plant aspartic proteinase (AP) from Cynara cardunculus L., has been investigated by high-sensitivity differential scanning calorimetry, intrinsic fluorescence and circular dichroism spectroscopy, and enzymatic activity assays. Even though the thermal denaturation of cardosin A is partially irreversible, valid thermodynamic data can be obtained within a wide pH region. Also, although cardosin A is a heterodimeric enzyme its thermal denaturation occurs without simultaneous dissociation to unfolded monomers. Moreover, in the 3-7 pH region the excess heat capacity can be deconvoluted into two components corresponding to two elementary two-state transitions, suggesting that the two polypeptide chains of cardosin A unfold independently. Detailed thermodynamic and structural investigations of cardosin A at pH=5.0, at which value the enzyme demonstrates maximum stability and enzymatic activity, revealed that after thermal denaturation the polypeptide chains of this protein retain most of their secondary structure motifs and are not completely hydrated.